Technological innovations for business, education and sustainability - Hamdan, Allam; Khamis, Reem (Technological innovation and sustainability for business competitive advantage, 2024)
Awareness of the essential skills required for thriving in the job market is necessary for educators and employers. Shedding light on the role of industry in promoting work-based learning, Technological Innovations for Business and Education Sustainability considers how technology has both transformed the business landscape, and how it might continue to do so in future. Harnessing the potential of innovative Industry 4.0 technologies such as the Internet of Things (IoT) and Artificial Intelligence (AI) for sustainable business models, contributors rethink core skills required to meet the changing needs of the work environments in terms of modes of education and workplace ethics, as well as the implications of these constantly evolving technologies for employers and workplaces. Chapters analyse in detail how rapidly advancing technologies have already affected recruitment, retail, banking, the oil and gas industry, insurance, financial services, advertising, childhood obesity, human resources and organizational management, small- and medium-sized enterprises (SMEs), cloud computing and more. Fulfilling a growing need for aligning business strategy and educational curriculums with the evolving skills required for business workplaces, Technological Innovations for Business and Education Sustainability presents a thorough understanding of how business, education and technology can enable current and future leaders to contribute positively to the digital transformation currently in play across the globe.